Macroflora diversity of the Riparian Zone of Taft River, Samar, Philippines - Bingco, Vanessa C.; Mahinay, Teresa S. (Tacloban City Vanessa C. Bingco, 2010)
A quantitative survey of the vegetation on the riparian zone of the Taft River in Samar Island has been undertaken on January-February, 2010. The aim of the research was to document quantitatively the vegetation of the riparian zone of Taft River by defining the species diversity that exist on the riparian area of the river. Initially, the river was mapped, and then 3 stations were established at the study site. The upstream station was established at Sitio Concord, Brgy. Bagacay in Hinabangan, Western Samar. The midstream station was established at Brgy. Malinao in Taft, while the downstream station was established at Brgy. Gayam in Taft, Eastern Samar. At each station, a 50x20 m quadrat was established on opposite banks of the river using the vegetation community monitoring protocol for wetlands. Plant species found in each quadrat were collected and brought to the University of the Philippines Visayas Tacloban College research laboratory for identification. All plant species identified were verified at the Visayas State University herbarium. The vegetation of the riparian zone of the Taft River consists of 56 plant species from 29 families of the plant kingdom. Mimosa pudica were observed to have the highest relative frequency. Moreover, the herbs dominate the study site, followed by trees, then grasses, and lastly by shrubs.
The downstream station is the most diverse of the stations, followed by the upstream station, while the least diverse is the midstream station.
Undergraduate thesis (B.S. Biology)--University of the Philippines, Tacloban.
Keywords: Science and technology